Suasana baharu perkahwinan kita - Halim, Noratikah Halim (Universiti Teknologi MARA, Perak, 2022)
Suasana Baharu Perkahwinan Kita act as public service announcement by Majlis Keselamatan Negara to encouraging people’s awareness towards the new norms in marriage. The information is carried out in collaboration with Kementerian Kesihatan Malaysia. This campaign will be launch in Bahasa Melayu.